Bank-specific characteristics and monetary policy transmission: the case of Italy, - Leonardo Gambacorta (European Central Bank (ECB), 2001)
This paper tests cross-sectional differences in the effectiveness of the bank lending channel of monetary policy in Italy from 1986 to 1998 using a panel approach. After a monetary tightening the decrease in deposits subject to reserve requirements is sharper for those banks that have less incentive to shield the effect of a monetary squeeze: small banks characterized by a higher ratio of deposits to loans and well-capitalized banks that have a greater capacity to raise other forms of external funds. As to lending, size does not affect the banks' reaction to a monetary policy impulse. This can be explained by a closer customer relationship, which provides an incentive for small banks, which are more liquid on average, to smooth the effects of a tightening on credit supplied. Banks' liquidity is the most significant factor enabling them to attenuate the effect of a decrease in deposits on lending.
Keywords: E44; E51; E52; 330; bank lending channel; monetary policy; transmission mechanisms